ANALYSIS OF CASH CONVERSION CYCLE TO COMPANY LIQUIDITY & WORKING CAPITAL (A CASE STUDY OF PT. GISTEX TEXTILE INDONESIA) (The Indonesian Journal of Business Administration, 2021)
Indonesia textile industry in 2019 is under pressure due to the large number of imports entering the local market, which makes industrial sales depressed that had Impacted on the performance and growth of the textile declining. PT. Gistex, a company engaged in the textile industry, is also experiencing the same pressure as the industry. The company's had a poor performance reflected in the Cash Conversion Cycle Indicator, which is getting higher each period and the value of liquidity is decreasing. Cash Conversion Cycle should be a concern for the company, namely improving company performance and improving shareholder welfare. So it is important to find an improvement in the Cash Conversion Cycle for PT. Gistex so as to improve the welfare of the owner. The analysis is carried out to obtain an indicator of the target improvement for the company, namely by forecasting for 5 years with various different scenarios and adjusting to market conditions. Industry cash conversion cycle benchmarks are also important, benchmark uses a population of listed companies on the stock exchange. The issuer's data and performance are looking for the Cash Conversion Cycle turnover rate for various aspects such as Receivable Turnover, Inventory Turnover and Payable Turnover. As a reference, the company must improve, namely receivable turnover and inventory turnover. The improvement in terms of receivables and inventory turnover aspects based on industry performance will be used as a reference for companies in determining their business and management strategy. The results obtained after using these references are that the company can improve its profitability and liquidity performance. Important for PT. Gistex to increase the cash conversion cycle so as to increase the shareholders welfare, the company must control, manage and monitor the driving factors of the cash conversion cycle.Keyword: Cash Conversion Cycle, Receivable Turnover, Inventory Turnover, Shareholder Wealth